Family, archive, and the posttraumatic imaginary: an analysis of the role of archival material in the personal documentaries stories we tell, the Imam and I, and grandpa Ernest speaks - Bazil,Madeleine (Centre for Film and Media Studies, 2023)
My short documentary, Grandpa Ernest Speaks (2021), is the creative research portion of my master's degree submission. The film is heavily influenced by post-structuralist theory regarding the archive as an experiential entity as well as posttraumatic cinema discourse (in particular, Joshua Hirsch's phases of posttraumatic cinema). This critical reflection therefore investigates the intersection of these two theoretical paradigms: looking at how archival materials may specifically be used in personal documentary films dealing with family/ancestral trauma and posttraumatic memory, and positing that these films' engagement with the archive fits into the larger framework of posttraumatic cinema. I reflect on Grandpa Ernest Speaks in conversation with two other personal posttraumatic documentaries, The Imam and I (dir. Khalid Shamis, South Africa, 2011) and Stories We Tell ( dir. Sarah Polley, Canada, 2012). I conduct a semiotic and content analysis of portions of all three films in order to both situate them within the posttraumatic imaginary-specifically, within Hirsch's second phase-and examine the role of the archive and artefacts in each. In doing so, I confront the question of record vs. representation in documentary, and argue that-in the archival-based posttraumatic documentary-the distinction between the two lies in the way that the artefact is interpreted or contextualised via meta-textual captioning. This study demonstrates that posttraumatic memory may be nonlinear and non-chronological. The analysis of my film and the two additional case study films examines how this complication of past and present, archival and contemporary, is articulated onscreen: conveying the transmutation of memory as well as the ongoing and self-reflexive act of contributing to the familial archive.